Explaining changing individual identity: two examples from the financial crisis. (15th August 2019) - Davis, John B.
This paper outlines a framework for explaining change in agent identities, and uses the recent financial crisis to illustrate it by comparing two examples of identity change brought about by the crisis. The agent identity theory employed is the idea of a having capability for keeping a self-narrative or autobiographical account of oneself. This is developed in terms of two ways individuals identify with social groups and in terms of individuals performing a self-concept. The two examples of identity change concern sub-prime homeowners and bank depositors. The paper closes with comments on the role of identity analysis in a pluralistic economics.